In vitro mass propagation and conservation of Nilgirianthus ciliatus through nodal explants: A globally endangered, high trade medicinal plant of Western Ghats. (4th March 2017) - Rameshkumar, R.; Largia, M. J. V.; Satish, L.; Shilpha, J.; Ramesh, M.
Abstract: Nilgirianthus ciliatus is a globally endangered aromatic slender shrub of Western Ghats with extensive applications in Ayurveda. It is endangered due to its indiscriminate collection and overexploitation to meet the requirements of the pharmaceuticals. This study deals with the preservation of this endangered plant through in vitro nodal culture. Nodal explants were initially cultured on Murashige and Skoog (MS) medium supplemented with 6-benzylaminopurine (BA) or 6-furfurylaminopurine individually for primary shoot induction. For multiple shoot induction, primary shoots were transferred onto MS medium containing BA individually or in combination with auxins. Clusters of multiple shoots (up to 24.3) occurred with highest frequency (93.2%) on MS medium fortified with BA (3 mg l −1 ) and indole-3-acetic acid (0.1 mg l −1 ). In vitro regenerated plantlets were rooted on half-strength MS medium with maximum rooting frequency (82.2%) obtained in the presence of indole-3-butyric acid (1.0 mg l −1 ). The rooted plantlets were acclimatized to soil with 100% survival rate. Results of this study allowed us to develop an efficient regeneration system that will permit to carry out restoration programmes of N. ciliatus in Western Ghats. In future, this protocol will be an invaluable tool to produce synthetic seeds for cryopreservation and long-term conservation.